2020
DOI: 10.3390/cells9040952
|View full text |Cite
|
Sign up to set email alerts
|

CCN-Based Therapeutic Peptides Modify Pancreatic Ductal Adenocarcinoma Microenvironment and Decrease Tumor Growth in Combination with Chemotherapy

Abstract: The prominent desmoplastic stroma of pancreatic ductal adenocarcinoma (PDAC) is a determinant factor in tumor progression and a major barrier to the access of chemotherapy. The PDAC microenvironment therefore appears to be a promising therapeutic target. CCN2/CTGF is a profibrotic matricellular protein, highly present in the PDAC microenvironment and associated with disease progression. Here we have investigated the therapeutic value of the CCN2-targeting BLR100 and BLR200, two modified synthetic peptides deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…In a phase I and II study, pamrevlumab, enhanced gemcitabine activity in locally advanced pancreatic cancer patients ( 102 ). Similarly, another study also demonstrated the use of peptides targeting CTGF alone and in combination with gemcitabine in reducing tumor size ( 103 ).…”
Section: Growth Factors and Chemoresistancementioning
confidence: 96%
“…In a phase I and II study, pamrevlumab, enhanced gemcitabine activity in locally advanced pancreatic cancer patients ( 102 ). Similarly, another study also demonstrated the use of peptides targeting CTGF alone and in combination with gemcitabine in reducing tumor size ( 103 ).…”
Section: Growth Factors and Chemoresistancementioning
confidence: 96%
“…65 These promising results have also granted this regimen for the Phase III clinical trial recently. 65 A study from Resov et al 66 investigated two synthetic peptides targeting CTGF and showed an increased tumor inhibition when administered in combination with gemcitabine. It is worthy to note that the peptide did not improve the gemcitabine level in the PDAC tumor model.…”
Section: Modulation Of Tumor Stroma Targeting Cafs To Improve Penetrationmentioning
confidence: 99%
“…We focused on the mixed-prognostic interactions because these interactions may be involved interactions, we highlight the LR interaction, CTGF:LRP6, due to the increasing interest in anti-CTGF therapy (Fig 5b) (29,30). CTGF is inferred to be secreted not only from M(2), but also iFibs from within the same scREMI-LUAD community (p-val < 0.1)(Fig 5c and Supp Fig 5a-b).…”
Section: In-situ Experimental Validation Of Ctgf and Lrp6 Co-localization Among Malignant Subpopulations In Luadmentioning
confidence: 99%